A Review Paper on Digital Advertising (International Journal of Innovative Research in Computer Science & Technology, 2021)
Despite the constantly increasing  spending on digital advertising, the efficiency of the  ecosystem's operating is becoming more apparent. This is  because just a tiny portion of the money spent by  businesses on different kinds of digital advertising yields  the desired outcomes. In today's corporate world, the term  "digital marketing" is a buzzword. Because of its cost  efficiency, digital advertising, which is a small portion of  it, has become the most frequently discussed and worked  on. Communication between the customer and the seller  has taken on a completely new meaning in the internet  era. As more individuals become computer aware, the  internet is developing as a powerful advertising medium.  The purpose of this article is to explain the efficacy of  digital advertising in terms of generating awareness,  interest, and preference, as well as giving product  information and encouraging purchase. The most popular  ad formats is also explained. Consumers consider digital  advertising to be helpful and interesting, according to the  research.
Keywords: Advertisements; Customer; Digital; Information; Product